Le rêve dans Le dernier gardien de l’arbre de Jean-Roger Essomba - Miconi, Jada (Ponti/Ponts, 2021)
The importance of the dreamlike theme in Jean Roger Essomba’s novel Le dernier gardien de l’arbre derives not only from its intense narrative presence, but also from of its textual specificity. In this article I analyze the dreams experienced by the main characters and I highlight the function of these events in the text’s structure: their novelistic representation is closely linked to the universe of ancestral beliefs and allows the Western reader a kind of initiation into African Tradition. Littérature francophone, roman africain, thème onirique, Jean-Roger Essomba, Afrique, Tradition, surnaturel, ésotérisme, temporalité cyclique, rencontre culturelle, initiation.